American Telemedicine Association: 19th Annual International Meeting & Tradeshow - Jordana Bernard (International Journal of Telerehabilitation)
The 2014 American Telemedicine Association (ATA 2014) Annual International Meeting & Exposition, will be held May 18-20, 2014 in Baltimore, Maryland. ATA 2014 will bring together healthcare professionals, leading telemedicine programs, and industry. This meeting has been the premier forum for professionals in the telemedicine, telehealth and mHealth space for over 19 years. ATA 2014 is on course to be the largest ATA meeting ever, with over 6,000 projected attendees. The exhibit hall will feature nearly 300 of the leading vendors in remote healthcare technologies. The program will include 500 educational sessions and posters highlighting the latest innovations, applications and research in telemedicine. The educational sessions at ATA 2014 will offer training, information, and updates on issues vital to the practice and industry of telemedicine.   Detailed program information--including courses, sessions and Continuing Medical Education (CME) information--will be available January 2014 at: http://www.americantelemed.org.